An Overview of Maternal Knowledge, Parenting Practices, and Environmental Sanitation in Relation to Stunting Among Children Aged 24–59 Months: A Study in The Working Area of Karang Intan 2 Public Health Center, Banjar Regency - Nazarul Akhta, M.; Abdurrachim, Rijanti; Aprianti; Yanti, Rusmini (Jurnal Riset Pangan dan Gizi, 2025)
The prevalence of stunting in Banjar Regency in 2023 increased to 30.1%, with Karang Intan 2 Public Health Center being one of the areas with a high stunting rate, at 31.65%. This study aims to describe maternal knowledge, parenting patterns, and environmental sanitation in relation to stunting among children aged 24–59 months in the area. This is an observational study with a descriptive approach, conducted from February to April 2025 in the working area of Karang Intan 2 Public Health Center. The variables studied include maternal knowledge, parenting patterns, and environmental sanitation related to stunting in children aged 24–59 months. A sample of 90 respondents was selected using Slovin’s formula. Data were collected through structured questionnaire interviews, observation of home sanitation, and documentation. Univariate analysis was used for data analysis. The results show that the majority of mothers have poor knowledge (52.2%), poor parenting patterns (46.7%), and sanitary conditions that do not meet standards (54.4%). Stunted children account for 41.1% of the total sample. Improving nutrition education for children, guidance on appropriate parenting practices, and enhancing environmental sanitation are important steps to reduce stunting in the working area of Karang Intan 2 Public Health Center, Banjar Regency.